Hubungan Kelembagaan antara Pengemudi dan PT GoTo Gojek Tokopedia Tbk: Pendekatan Teori Kontrak - Anisa Fitria Utami; Arum Indiharwati; Ary Fauziah Amini (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2026)
This study aims to analyze the institutional relationship between drivers and the PT GoTo Gojek Tokopedia Tbk within the framework of contract theory. The main focus is to examine how platform-based partnership contracts shape work dynamics, risk distribution, and potential imbalances between the company and drivers. Using a qualitative case study approach, in-depth interviews with five Gojek drivers selected purposively. Data were analyzed thematically and validated through source triangulation. The findings reveal that the partnership represents an incomplete contract, characterized by information asymmetry, moral hazard, and hold-up issues. While pengemudis enjoy flexible working hours, they bear the entire economic risks without sufficient social protection. The noverlty of this research lies ini applying contract theory to the Indonesian gig economy, highlighting algorithmic transparency and risk distribution dimension rarely explored in previous studies. These insights enrich institutional economics literature wihile offering empirical foundations for goverment regulations that are more equitable in protecting gig economy workers.